Heterogeneous Government Spending Multipliers in the Era Surrounding the Great Recession - Marco Bernardini; Selien De Schryder; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2017)
We use a novel quarterly dataset of U.S. states to examine the dynamics and determinants of relative government spending multipliers in the decade surrounding the Great Recession. We find average multipliers that are similar to those that have been reported for the decades preceding the crisis, but this masks substantial heterogeneity. First, average cumulative multipliers were around 2 in the impact quarter, but declined to less than 1 after one year. Second, implied relative multipliers ranged between 0 and more than 4 across states at particular points in time, as well as for the same state at different moments within the sample period depending on the individual state's stance of the business cycle, household indebtedness and the interaction of both conditions. Finally, we provide evidence that, controlling for total expenditures, a mere redistribution of government spending across states did also had a significant influence on the aggregate U.S. economy due to cross-state heterogeneity of the effects.
Keywords: C23; E32; E44; E62; 330; fiscal multiplier; household debt; Great Recession; regional redistribution